Folate-conjugated human serum albumin-encapsulated resveratrol nanoparticles: preparation, characterization, bioavailability and targeting of liver tumors. Issue 1 (4th December 2019) - Lian, Bolin; Wu, Mingfang; Feng, Ziqi; Deng, Yiping; Zhong, Chen; Zhao, Xiuhua
Abstract: This work investigated the preparation of specific targeted drug delivery systems in cancer chemotherapy by folate conjugated human serum albumin nanoparticles encapsulated resveratrol (RES) nanoparticles (FA-HSA-RESNPs). FA was coupled to HSA, and RES was encapsulated in FA-conjugated HSA by high pressure fluid nano-homogeneous emulsification. The average particle size and polydispersity index of NPs prepared under optimal conditions were 102.1 ± 4.9 nm and 0.001. The drug capsulation efficiency and drug loading efficiency were 98.36 and 14.66%, respectively. The analysis of the results of the physical characterization showed that the RES was present in the FA-HSA-RESNPs in an amorphous state. In vitro drug-release study showed that the NPs can release the drug persistently and slowly. The inhibition rate of FA-HSA-RESNPs and RES was detected using the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide method to be 110.8 and 157.2 μM, respectively. The targeting ability of the FA-HSA-RESNPs for the HepG2 cell was measured by fluorescein isothiocyanate-modified albumin techniques. The uptake rate of FA-HSA-RESNPs was higher than that of the original RES. By using near-infrared imaging, in vivo activity was labeled with Cy5 fluorescent FA-HSA-RESNP confirmed FA-HSA-RESNP tumor-targeting ability. The intravenous administration bioavailability of FA-HSA-RESNPs was about 5.95-fold higher than that of the original RES. Graphical Abstract: